Bibliometric Analysis of Publications Related to Bhutan, 1894-2022. - Wangdi, Sonam (Journal of Bhutan Studies)
This study provides an overall growth of Bhutan-related literature to understand scientific productivity of the nation. This paper aims to assess scientific productivity of Bhutan in terms of the country's literature growth in the international arena and to establish baseline information on research trends and hotspots, benefiting both scholars and policymakers. The bibliometric technique was employed to analyze the evolutionary trend, identify key institutions, prolific authors, leading countries, and prominent themes, while also highlighting emerging areas of research in Bhutan. A total of 4145 Bhutan-related publications were identified and retrieved from the Scopus database (1894-2022). The result showed that the growth of Bhutan-related literature increased significantly over the last decade with a maximum publication in 2021 (n=461). Of the total, about 72% consists of articles, whereas conference reviews and data papers were minimum. Journal of Threatened Taxa published the highest number of literature. Among the Bhutanese institutions, the Jigme Dorji Wangchuck National Referral Hospital (JDWNRH) published the highest (n=398) total number of publications, while the Ministry of Agriculture and Forests (MoAF) received the highest network of publication connections. Keyword analysis revealed that the field of taxonomy, new species and climate change were dominant in Bhutan's research landscape and are expected to remain prominent in the future. The findings revealed that Bhutan published the highest number of literature among the top ten countries, and ranked the highest number of corresponding authors from multiple countries (n=159). However, the international collaboration rate in literature publication was low compared to Australia, Thailand and Nepal.